New prognostic factors in breast cancer; review of the literature - Piotr Pierzchała, Robert; Pasz-Walczak, Grażyna; Jeziorski, Arkadiusz (Contemporary Oncology/Współczesna Onkologia, 2004)
Prognostic factors are features of neoplasm’s biology, that allow us to predict the clinical course of the disease. In 1994 the College of American Pathologists proposed dividing prognostic factors into three groups. The first group comprises classic markers, whose prognostic value is fully documented and which are widely used for planning of treatment and evaluation of prognosis. The second group is composed of markers being currently under evaluation in clinical trials. In these trials, new prognostic factors are compared with the classic ones. The third group is composed of markers which do not fulfill criteria of markers from the first and second groups. Prognostic value of markers from the third group has not been documented yet. Classic prognostic factors in breast cancer seem to have a limited value; breast cancers with similar prognostic factors may have different clinical course. Therefore it is necessary to search for new markers, and to evaluate their prognostic value. Twenty two reports published from 1999 to 2004 were analyzed. Authors analyzed and discussed the predictive value of metalloproteinases and their inhibitors, cyclin D1, E-cadherin, cathepsin D, NM-23, thioredoxin, endonucleases AP1/Ref1 and AP2, cyclooxygenase 2, Minichromosome Maintenance (MCM), kallikreins and P21. Published results of studies are not univocal. Differences might be caused by the use of various study populations and different methods of analysis. It seems that further studies on new prognostic factors are warranted.